2020
DOI: 10.3390/foods9030335
|View full text |Cite
|
Sign up to set email alerts
|

Production of Probiotic Passion Fruit (Passiflora edulis Sims f. flavicarpa Deg.) Drink Using Lactobacillus reuteri and Microencapsulation via Spray Drying

Abstract: Probiotic foods offer many benefits to human health, causing increased interest in the development of new food products that exploit such benefits. However, traditional dairy foods are being replaced by other non-dairy foods to provide additional sources of benefits provided by bioactive molecules. Therefore, the objective of the present work was to study the production process of a probiotic fruit drink and then microencapsulate the probiotic pulp to stabilize the drink further. Passion fruit pulp (Passiflora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In the present study, Table 2 showed a growth rate variation of 0.27 to 0.54 h −1 in the experiments carried out at temperatures of 35 and 25 °C, respectively. This effect is observed in Figure 2a Under ideal conditions, bacteria are the microorganisms with the highest growth rate and may have a generation time (tg) of less than 1 h [32]. The generation time, which is the parameter that indicates the time required for the duplication of the cell population, ranged from 1.28 to 2.56 h in the present study.…”
Section: Optimization Of Fermentation With L Salivariusmentioning
confidence: 50%
See 4 more Smart Citations
“…In the present study, Table 2 showed a growth rate variation of 0.27 to 0.54 h −1 in the experiments carried out at temperatures of 35 and 25 °C, respectively. This effect is observed in Figure 2a Under ideal conditions, bacteria are the microorganisms with the highest growth rate and may have a generation time (tg) of less than 1 h [32]. The generation time, which is the parameter that indicates the time required for the duplication of the cell population, ranged from 1.28 to 2.56 h in the present study.…”
Section: Optimization Of Fermentation With L Salivariusmentioning
confidence: 50%
“…Reducing sugars are simple sugars, and their presence in filmogenic solutions favors the development of lactic acid bacteria, which use simple sugars as the main source of energy. These values are different from the amount of sugars found in milk (4.49 g of lactose/100 g) [36] and in fruits such as passion fruit (4.86 g of glucose/100 g) [32], which have been studied for the production of probiotic foods. However, inulin is a widely studied prebiotic that acts as a substrate for the development of microorganisms, enabling a favorable environment for the growth of L. salivarius in filmogenic solutions.…”
Section: Optimization Of Fermentation With L Salivariusmentioning
confidence: 82%
See 3 more Smart Citations